Determinant of the intention to use marketing analytics for SMEs performance among east coast region of Malaysian entrepreneurs - Ashraf Danieal Johari; Dhiviya Mogana Kumar; Julianah Julkepli; Noor Syahidah Mursyidah Mohd Sharif; Muhammad Hafizam Ismail (2024)
The spread of the use of marketing analytics has led to a positive perception of Social Media Marketing Analytics among SMEs, especially in the East Coast region of Malaysia (ECRM) and created a potential impact on business performance. The widespread embrace of social media marketing has changed the way businesses promote themselves, with small businesses enjoying a huge advantage as a result. The primary objectives were to examine the impact of technology factors (TF) and SMEs performance (SP), to investigate the relationship between organizational factors (OF) and SP and, to assess the influence of environmental factors (EF) and SP in the ECRM. The researcher focuses on the relationship between the independent variables (technological, organizational, and, environmental) and dependent variables (SMEs performances). This study uses a quantitative methodology to study the behavior, views, and intentions of SMEs entrepreneurs in the ECRM, regarding their understanding of the use of marketing analytics on SP using the online questionnaires in Google Forms. A total of 400 respondents participated in this study. The analysis utilized the Statistical Package for the Social Science (SPSS) version 26, encompassing the descriptive analysis, reliability analysis, normality testing, spearman correlation, multi-linear regression, and hypothesis testing. The result revealed a positive and significant relationship between TF, OF, and EF and SP in the ECRM. The findings revealed that all the hypotheses were accepted. For the future work, it is suggested to apply the qualitative data as the other methods for collecting the data. It is known to support the results of the study.